Smart Utilization of Ground Water Resources in Agriculture Field using the Internet of things - DB , Kale; A, Taneja; D, Rewardikar (International Journal of Computer Sciences and Engineering, 2019)
Ground water resources are a lifeline for living begins on this earth. These resources have been used in the agriculture field, drinking water and industry sector. The researcher believes that India is gradually moving towards the excess use and contamination of groundwater. In India 89% of ground water used in the irrigation sector, making it the highest category user in the country. Last decade, there has been a continued increase in ground water utilization for irrigation and it would decrease surface water level. In the conventional systems to farmer personally visited Wells or tanks checking water availability and check irrigation condition in the field by focusing various aspects such as observe water Level in wells or tanks, pump condition for on or off, for testing water quality required the manual collection of water samples and detect any intrusion in agriculture field. This older system had drawbacks such as time-consuming, wastage of ground water in irrigation. So to mitigate all drawbacks, there must be a requirement of effective utilization of ground water resources in the agriculture field using the Internet of things (IoT). Propose work which makes use of various technologies like, Internet of things, sensors, actuators, and WiFi module. It will provide many services to the farmer in agriculture field include automatic pump on/off the system, which make help to save the water without human interaction, finding the amount of water using water level sensors, weather observation, Intrusion detection at water resources area and test water quality of ground water, etc.